(untitled) (INNOVATIVE ECONOMY, 2025)
Semaniuk V.Z., Shpak V.B. MANAGEMENT OF ENVIRONMENTAL RISKS IN THE ACCOUNTING SYSTEM OF ENTERPRISES IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT AND THE CIRCULAR ECONOMY Purpose. The aim of the article is to substantiate the theoretical foundations and develop practical approaches to integrating environmental risk management into the strategic accounting system of enterprises in the context of sustainable development and the circular economy.of theoretical foundations and the development of practical approaches to integrating environmental risk management into the strategic accounting system of enterprises in the context of sustainable development and the circular economy. Methodology of research. The research applies a systematic approach for the comprehensive consideration of management accounting as an integrated system for environmental risk management. Methods of comparative analysis and synthesis were applied to generalize the theoretical foundations of sustainable development, the circular economy, and existing accounting models (EMA, circular accounting). For the quantitative assessment of environmental risks, an algorithm for their identification, classification, and calculation of risk indices is proposed based on risk-oriented accounting and integrated digital data. The method of economic and mathematical modeling was utilized to formalize the calculation of individual and aggregated risk indicators. Findings. The article develops a risk-oriented model of environmental risk accounting that involves identifying the sources of environmental threats, classifying them into strategic, operational, and financial categories, and quantitatively assessing their impact on enterprise performance. Formalized methods for calculating individual and aggregated risk indicators based on integrated data from digital monitoring systems (ERP, IoT, LCA) are proposed. A framework for management reporting that reflects risk metrics, including KPIs of resource intensity, financial losses, waste, and risk flow indices, has been established. It is determined that the implementation of such a system enables the creation of an integrated base for strategic environmental risk management, assessment of their impact on the enterprise, and the formation of reserves to cover potential losses. The need to build an information and analytical architecture based on modern data processing technologies (ETL, Data Lake, OLAP) is substantiated, ensuring real-time formation of risk metrics and improving the accuracy of management decisions. Originality. The theoretical and methodological foundations of strategic accounting have been improved through the integration of a risk-oriented model of environmental risk management. A formalized approach to calculating the aggregated environmental risk of an enterprise and a system of KPI indicators for real-time risk monitoring are proposed. Practical value. The developed methodology can be used by enterprises to build a strategic accounting system that ensures the digitalization of environmental risk management, improves resource efficiency, enables ESG reporting, and ensures compliance with the requirements of the European Green Deal. Key words: strategic accounting, management accounting, environmental risks, circular economy, ESG, digital monitoring, risk-oriented system.